The Effectivity of “Pokdarwis” Role on Successfully Marketing of Tourism Village Towards “Mega Tourism: Batu City For The World” - Syarif Hidayatullah; Ike Kusdyah Rachmawati; Umu Khouroh; Irany Windhyastiti; Irany Windhyastiti (International Conferences SDGs 2030 Challenges and Solutions, 2030)
Tourism sector is the one of the leading sectors of Batu City. To enhance the spirit of tourism sector development in the international sphere, in 2017 Government of Batu City launched the slogan "Mega Tourism : Batu City For the World". To facilitate the achievement of the target of marketing Batu City in the international world, Government of Batu City can not rely solely on artificial tourism conducted by private parties such as Jatim Park Group, but also have to develop various nature tourism or other uniqueness of Batu City. The Government of Batu City can explore the natural attractions or the uniqueness of local tourism through the development of Rural Tourism. The development of Tourism Village in Batu City, the participation of the villagers through the formation of the Community Based Tourism called Pokdarwis. This research is a case study on Pokdarwis in Village of Pesanggrahan, Junrejo and Dadaprejo in Batu City. Analytical techniques used in this study is descriptive analysis. Based on the results of data analysis in three locations of tourism villages shows that Pokdarwis still has not played an effective role in tourism activities. In general, Pokdarwis in three villages faced obstacles in the implementation of activities in terms of: 1) Pokdarwis members still lacked awareness about the importance and benefits of increasing tourism activities in the region, 2) Pokdarwis members still due independently marketing and promoting their personal business, not their region; 3) The Government of Tourism Department does not coordinate and assist them intensively. These three things, hampered the development of tourist villages. In fact in these three villages each has excellent potential that can be developed. Therefore, to improve the role of Pokdarwis it is suggest that: 1) The leader of Pokdarwis should be given to village officials who have the authority to direct and control activities and have a high interest and motivation in improving the tourism sector, 2) Government of Tourism Department must conduct socialization and training to open the the community mind about the importance and benefits of tourism activities development in the region, 3) Goverment of Tourism Department should conduct intensive coordination and assistance. In general it can be concluded that the existence of Pokdarwis needs to be supported and nurtured continuously, so that it can play a more effective role in mobilizing public participation in creating conducive environment and atmosphere to improve and develop tourism activities around tourism destinations.